Bovine Papillomavirus Genotypic Diversity and a Putative Novel Viral Type in Ecuador - Diego J. Carvajal-Reina; Fausto Bedoya-Páez; Mónica Salomé Guerrero-Freire; Yanua Ledesma; David Vasco-Julio; Jacobus H. de Waard; Armando Reyna-Bello (Veterinary Sciences, 2025)
Bovine papillomatosis, caused by a growing group of bovine papillomaviruses (BPVs), is a disease with benign proliferative lesions (papillomas) that may progress to malignancies due to immunological, environmental, or viral factors. This study investigated BPV type diversity in cattle from the Province Santo Domingo de Tsáchilas in Ecuador. Warty lesions were collected from 30 cattle across eight farms. Nucleic acids were extracted using a silicon dioxide-based method, and the partial L1 gene was amplified with PCR. DNA sequences were analyzed using maximum likelihood phylogenetics. Fifty-seven warty lesions yielded ten well-known BPV types: BPV1, BPV2, BPV4, BPV6, BPV8, BPV9, BPV10, BPV13, BPV14, and BPV42. Recently described viral types, BPV-CR2 from Costa Rica and BPV/BR-UEL08 from Brazil, were also detected, alongside a putative novel viral type, BPVEC2024-6-22.1—likely belonging to the genus Xipapillomavirus. This genus had the highest overall count. In contrast, Deltapapillomaviruses were found across all sampled farms. This study underscores BPV diversity in this localized region of Ecuador, and includes genotypes linked to cancers such as enzootic hematuria. The findings provide important epidemiological insights, contributing to vaccine development or immune therapy and improved disease management.